Development of Web-Based Computer Laboratory Management Information System at SMKS Pertiwi Batam - Hanafi; Novi Hendri Adi; Agung Budi Kusuma; Sai Kham Le (Researcher and Lecturer Society, 2023)
Development of Computer Laboratory Management Information System at SMKS Pertiwi Batam is an application to support the performance of related institutions. Lack of data collection and the absence of supporting applications and data that is still stored in the form of archives and computers manually. Information systems are designed based on websites using the codeigniter programming language and MySQL database. While the development of the research system uses the waterfall method with the stages of requirements, design, implementation, verification, and maintenance. This information system serves as a means of sharing information about the inventory of computer laboratory equipment, the use of computer laboratories, and schedules regarding the use of computer laboratories. With this information system, the agency will be easier in collecting inventory data, using and scheduling computer laboratories. As well as the need to make monthly reports on computer laboratory data.